\(\sqrt{2x-3}+6=2x+\sqrt{x}\)
\(\Leftrightarrow\sqrt{2x-3}=2x+\sqrt{x}-6\)
\(\Leftrightarrow\left(\sqrt{2x-3}\right)^2=\left(2x+\sqrt{x}-6\right)^2\)
\(\Leftrightarrow2x-3=4\sqrt{x}.x+4x^2-23x-12\sqrt{x}+36\)
\(\Leftrightarrow4\sqrt{x}.x-12\sqrt{x}+36=-4x^2+25x-3\)
\(\Leftrightarrow4\sqrt{x}.\left(x-3\right)=-4x^2+25x-39\)
\(\Leftrightarrow\left[4\sqrt{x}.\left(x-2\right)\right]^2=\left(-4x^2+25x-39\right)\)
\(\Leftrightarrow16x^3-96x^2+144x=16x^4-200x^3+937x^2-1950x+1521\)
\(\Leftrightarrow x=3\)
Bài của Ball CTV thiếu ĐKXĐ vs Đk bình phương nên sai bét mà vẫn có đứa tk đúng -_- ngu học